Revealing conformational transitions in G-protein-coupled receptor rhodopsin upon phosphorylation - Jatana, Nidhi; Thukral, Lipi (Biochemistry, 2020)
G-protein-coupled receptors (GPCRs) have evolved as highly specialized cellular machinery that can dictate biological outcomes in response to diverse stimuli. Specifically, they induce multiple pathway responses upon structural perturbations induced at local protein sites. GPCRs utilize a concurrent strategy involving a central transmembrane topology and biochemical modifications for precise functional implementation. However, the specific role of the latter is not known due to the lack of precise probing techniques that can characterize receptor dynamics upon biochemical modifications. Phosphorylation is known to be one of the critical biochemical modifications in GPCRs that aids in receptor desensitization via arrestin binding. Here, we carry out all-atom molecular dynamics simulations of rhodopsin in a membrane environment to study its conformational dynamics induced upon phosphorylation. Interestingly, our comparative analysis of non-phosphorylated and phosphorylated rhodopsin structure demonstrated enhanced receptor stability upon phosphorylation at the C-terminal region that leads to the opening of the extracellular part of the transmembrane helices. In addition, monitoring the distinct number of phosphorylation states showed that having fewer phosphorylated residues does not bring about appropriate conformational changes in the extracellular region. Since phosphorylation results in receptor desensitization and recycling of the ligand, our findings provide significant insights into the conformational dynamics of the mechanism of ligand exit from the receptor.
Published: December 17, 2019
Gesehen am 03.03.2020